Mandibular odontogenic myxoma in a paediatric patient. Issue 10 (30th October 2020) - Shupak, Raymond Patrick; Cho, Jason J
Abstract : Odontogenic myxoma (OM) are benign, locally aggressive tumours that are rarely found in the paediatric maxillofacial region. OMs derive from mesenchymal odontogenic tissue. We describe the management of a 3-year-old girl who presented with a large right-sided mandibular lesion. Her treatment included conservative excision, curettage and peripheral ostectomy. A literature review was performed which calls into question the dogmatic practice of resection with 1 to 1.5 cm margins. Treatment approaches to the OM could potentially be altered in the paediatric patient.